What Models and Tools can Contribute to a Better Understanding of Brain Activity? - Goodfellow, Marc; Andrzejak, Ralph G.; Masoller, Cristina; Lehnertz, Klaus (Frontiers in Network Physiology, 2022)
Despite impressive scientific advances in understanding the structure and function of the human brain, big challenges remain. A deep understanding of healthy and aberrant brain activity at a wide range of temporal and spatial scales is needed. Here we discuss, from an interdisciplinary network perspective, the advancements in physical and mathematical modeling as well as in data analysis techniques that, in our opinion, have potential to further advance our understanding of brain structure and function.